Shared Psychotic Disorder: A Case Report - Korkmaz, Sevda; Kuloglu, Murat; Bahceci, Bulent; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2010)
Shared psychotic disorder (folie a deux) is a rare disorder characterized by delusions and demonstrates intercultural differences. Cases reported in the literature have considerable persecution, reference and mystical delusions. However, erotomanic delusion has been rarely reported. In the present paper, we present a case, the daughter of a schizophrenic mother who has shared psychotic disorder accompanied by erotomanic delusion.
Keywords: Shared psychotic disorder; folie communique; erotomanic delusion